Mesoporous molecular sieve (MCM-41)-filled sodium alginate hybrid nanocomposite membranes for pervaporation separation of water-isopropanol mixtures - Bhat, S. D.; Naidu, B. V. K.; Shanbhag, G.; Halligudi, Shivaraj B.; Sairam, M.; Aminabhavi, Tejraj M. (Separation of Purification Technology, 2006)
Sodium alginate (NaAlg) and the inesoporous molecular sieve (MCM-41)-filled NaAlg nanocomposite membranes have been prepared by solution casting and crosslinked with glutaraldehyde. Pervaporation performance of the MCM-41-filled NaAlg membranes has been tested and compared with plain NaAlg membrane for dehydrating isopropanol at 30 degrees C. In the studied feed composition range of 10-50 mass% of water, 20 mass% MCM-41-loaded NaAlg membrane gave the highest selectivity ranging between 29,991 and 3332 in the range of feed water compositions of 10-50 mass%. Flux for the plain NaAlg membrane ranged between 0.067 and 0.340 kg/(m(2)h), while for 20 mass% MCM-41-filled NaAlg membrane, flux increased to 0.110 and 0.555 kg/(m(2)h). To the best of our knowledge, this is the first study reported on the membrane forming properties of an admixed hybrid composite of a mesoporous molecular sieve (MCM-41) with NaAlg used in dehydration of isopropanol, yielding high selectivity to water at higher loadings of the molecular sieve as a filler. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: flux and selectivity; nanocomposite membranes; pervaporation; sodium alginate; water-isopropanol